Focusing microparticles in microfludic channel using surface acoustic waves - Lum, Perry Jun Hui (2019)
Along the years, surface acoustic wave (SAW) has been integrated into lab-on-a-chip (LOC) microfluidic devices. SAWs were generated by meshing and zig-zag patterns of the interdigital transducers on a piezoelectric substrate. Standing surface acoustic waves (SSAW) are frequently used in microscale-level manipulations of microparticles.